Pengembangan Petani Organik melalui Pendekatan ABCD - Agus Salim Chamidi; Benny Kurniawan; Agus Nur Soleh (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Organic farming is being promoted to maintain the fertility of paddy fields. Farmers who are members of the Kadang Tani Sarwo Tulus (KTST) Ambal Kebumen have been implementing it since 2021. However, their existence pays little attention to its development strategy. This community service research aims to help the KTST Ambal develop themselves based on their assets and potential in a participatory manner. The method used is the Asset Based Community Development (ABCD) approach. As a result, they succeeded in building their own vision, mission, objectives, programs and activities. They even managed to carry out two activities, namely, making goat compost and product packaging and promotion training, and making a product promotion activities and organic rice market development. They succeeded in implementing participatory strategic management. Their success is supported by their partnership with IAINU Kebumen. Recommendations, strategic management analysis needs to be one of the analytical tools in implementing activities based on the ABCD approach. Campus (university) partnerships with the community need to be a model in strengthening the community.Pertanian organic tengah digalakkan untuk menjaga kesuburan lahan tanah sawah. Petani yang tergabung dalam Kadang Tani Sarwo Tulus (KTST) Ambal Kebumen pun melaksanakannya sejak 2021. Akan tetapi eksistensi mereka kurang memperhatikan strategi pengembangannya. Riset pengabdian ini bertujuan membantu KTST Ambal mengembangkan diri berbasiskan asset dan potensi mereka secara partisipatoris. Metode digunakan adalah pendekatan Aset Based Community Development (ABCD). Hasilnya mereka berhasil membangun visi, misi, tujuan, program, dan kegiatannya sendiri. Bahkan mereka berhasil melaksanakan dua kegiatan, yaitu, pembuatan pupuk kompos kambing dan pelatihan pengepakan dan promosi produk, dan kegiatan promosi produk dan pengembangan pasar beras organic. Mereka berhasil menyelenggarakan manajemen stratejik secara partisipatoris. Keberhasilan mereka didukung oleh kemitraan mereka dengan IAINU Kebumen. Rekomendasi, analisis manajemen stratejik perlu menjadi salah satu alat analisis dalam penyelenggaraan kegiatan berbasis pendekatan ABCD. Kemitraan kampus (universitas) dengan komunitas perlu menjadi model dalam penguatan komunitas.